Role of hormones in bone remodeling in the craniofacial complex: A review - Erin Grinde Tunheim; Hans Erling Skallevold; Dinesh Rokaya (Journal of Oral Biology and Craniofacial Research)
Background: Diseases such as periodontitis and osteoporosis are expected to rise tremendously by 2050. Bone formation and remodeling are complex processes that are disturbed in a variety of diseases influenced by various hormones. Objective: This study aimed to review and present the roles of various hormones that regulate bone remodeling of the craniofacial complex. Methods: A literature search was conducted on PubMed and Google Scholar for studies related to hormones and jawbone. Search strategies included the combinations (“name of hormone” + “dental term”) of the following terms: “hormones”, “oxytocin”, “estrogen”, “adiponectin”, “parathyroid hormone”, “testosterone”, “insulin”, “angiotensin”, “cortisol”, and “erythropoietin”, combined with a dental term “jaw bone”, “alveolar bone”, “dental implant”, “jaw + bone regeneration, healing or repair”, “dentistry”, “periodontitis”, “dry socket”, “osteoporosis” or “alveolitis”. The papers were screened according to the inclusion criteria from January 1, 2000 to March 31, 2021 in English. Publications included reviews, book chapters, and original research papers; in vitro studies, in vivo animal, or human studies, including clinical studies, and meta-analyses. Results: Bone formation and remodeling is a complex continuous process involving many hormones. Bone volume reduction following tooth extractions and bone diseases, such as periodontitis and osteoporosis, cause serious problems and require a great understanding of the process. Conclusion: Hormones are with us all the time, shape our development and regulate homeostasis. Newly discovered effects of hormones influencing bone healing open the possibilities of using hormones as therapeutics to combat bone-related diseases.